During host cell traversal and cell-to-cell passage, Toxoplasma gondii sporozoites inhabit the parasitophorous vacuole and posteriorly release dense granule protein-associated membranous trails. Issue 13 (November 2020) - Tartarelli, Irene; Tinari, Antonella; Possenti, Alessia; Cherchi, Simona; Falchi, Mario; Dubey, Jitender P.; Spano, Furio
Graphical abstract: Highlights: During host cell travrsal Toxoplasma gondii sporozoites reside in the parasitophorous vacuole. Traversing sporozoites posteriorly release GRA-positive membranous tails named SSTs. We provide the first known ultrastructural evidence of sporozoite cell escape and cell-to-cell passage. Abstract: Toxoplasma gondii has a worldwide distribution and infects virtually all warm-blooded animals, including humans. Ingestion of the environmentally resistant oocyst stage, excreted only in the feces of cats, is central to transmission of this apicomplexan parasite. There is vast literature on the host and T. gondii tachyzoite (proliferative stage of the parasite) but little is known of the host-parasite interaction and conversion of the free-living stage (sporozoite inside the oocyst) to the parasitic stage. Here, we present events that follow invasion of host cells with T. gondii sporozoites by using immunofluorescence (IF) and transmission electron microscopy (TEM). Several human type cell cultures were infected with T. gondii sporozoites of the two genotypes (Type II, ME49 and Type III, VEG) most prevalent worldwide. For the first known time, using anti-rhoptry neck protein 4 (RON4) antibodies, the moving junction was visualized in sporozoites during the invasion process and shortly after its completion. Surprisingly, IF and TEM evaluation revealed that intracellular sporozoites release, at their posterior end, long membranous tails, herein named sporozoite-specific trails (SSTs). Differential permeabilization and IF experiments showed that the SSTs are associated with several dense granule proteins (GRAs) and that their membranous component is of parasite origin. Furthermore, TEM observations demonstrated that SST-associated sporozoites are delimited by a typical parasitophorous vacuole, which is retained during parasite exit from the host cell and during cell-to-cell passage. Our data strongly suggest that host cell traversal by T. gondii sporozoites relies on a novel force-producing mechanism, based on the massive extrusion at the parasite posterior pole of GRA-associated membranous material derived from the same pool of membranes forming the intravacuolar network.